Peran Ibu dalam Pembentukan Kemandirian Anak Keluarga Nelayan - Septifani, Riski; , Dr. Moordiningsih, M.Si., Psi (2015)
The involvement of mother to build independent of children on fisherman family is a task, a must and a responsibility as a mother to help the process of her children to be independent. Such as some activities to make children gains, resolves, also do some work by himself. The aim of this research is to know and to describe mother's involvement to build independent of children in fisherman family. The subject of this research are 5 peoples who taken by purposive sampling with the characteristics: a) wife from fisherman's captain or common fisherman, b) has one child with the rate of age is about 2-6 years old, c) has their own house. This research is using interview and behavior checklist methode to collect data. Writers uses matrix and categorization to analyze data. The result of this research shows that on the process to build independent of children, on the begining, mother is learning about the independent of child, then mother prepare her children independences from age, children ability, weaning, then the differences of independences form. There is a difference about the form of independences. Independences of common fisherman children is higher than another. Then mother involvement are also as a teacher, do monitoring, and as a facilitator. But, there are some different factors among wife of fisherman's captain and wife of common fisherman that influence the process to build children independences, they are economics factor that influence wife of common fisherman and weaning factor that influence on wife of fisherman's captain in the process to build children independences.